A non-orientalist representation of Pakistan in contemporary Western travelogues - Pourgharib, Behzad; Hamkhiyal, Soleyman; Asl, Moussa Pourya (Penerbit Universiti Kebangsaan Malaysia, 2022)
Travel writings by Western visitors of the Orient have often been rebuffed for disseminating a stereotypical discourse on the people and the culture of the East. The rationale for the collective dismissal of such narratives, however, is built upon a limited canon whose myopic perspective creates a monolithic Orient. It is argued that since this dominant discourse leaves nearly no room for non-conformism, it has conveniently overlooked a large body of travel writings of western writers that adopt a non-Orientalist approach to appreciate cultural differences. To pursue this argument, the present study aims to explore Jürgen Wasim Frembgen’s At the Shrine of the Red Sufi: Five Days & Nights on Pilgrimage in Pakistan (2011) to examine how the autobiographical narrator’s travel accounts present an alternative narrative about the East that subverts prevailing discourses on travelogues as apparatuses to reinforce colonial/Western norms. To achieve this goal, the study benefits from Debbie Lisle’s (2006) theories on the cosmopolitan vision of a travel writer as well as Edward Said’s (1978) theory of Orientalism. Frembgen’s cosmopolitan vision throughout the narrative neutralizes negative perceptions about Muslim communities in Pakistan as uncultivated and declining by offering a counter view of the country that underscores its vibrant and positively transformative qualities. The celebration of Eastern culture and religion in Frembgen’s travel writing indicates the need for the re-examination of the Orientalist thought that has, wittingly or unwittingly, dismissed a significant segment of western works about the east in order to legitimize its theoretical and hypothetical cases.